Impact of Climate Change on Livestock-Centric Rural Development: Adaptive Strategies for Sustainable Agriculture - Gyawali, Krishna Prasad; Kharel, Sharad Mani (Saptagandaki Journal, 2024)
This study investigates the impacts of climate change on livestock-centric rural development in Gaindakot Municipality, Nepal. Livestock farming is the primary livelihood for most households, with 61% maintaining 20-40 animals and 25% owning large-scale operations with over 60 livestock. However, small landholdings (1-5 Kattha) present challenges to economic stability, underlining the need for support to improve productivity. Climate change has significantly impacted livestock health, with 42.9% of households reporting moderate effects and 35.7% experiencing severe impacts, leading to declines in livestock productivity. The study highlights the adoption of water conservation methods, such as drip irrigation, and climate-resilient practices, including drought-resistant fodder and resilient livestock breeds. However, barriers to the broader adoption of these practices, such as a lack of awareness and limited access to resources, were noted. The study also emphasizes stronger policy support and further interventions to promote sustainable agricultural practices. These findings underscore the importance of adapting to climate change through improved livestock management, resource conservation, and enhanced policy frameworks to safeguard rural livelihoods and food security.